(untitled) (American & British Studies Annual, 2023)
In the context of culture’s fascination with cats, the present article analyzes the use of felines in two pieces of fiction by the southern writer Jim Grimsley: the short story “The Cathouse Lovers” (1976) and his novel Comfort & Joy (1993 in German, 1999 in English). The two texts differ greatly in terms of the genre, period, as well as the role of cats in the story, yet both of them include the motif of cats that have a negative effect on the romantic and sexual relationships of their human protagonists.